Discovery of the Late Cretaceous Barru adakite in SW Sulawesi and slab break-off beneath the Central Indonesian Accretionary Complex. (1st July 2022) - Wu, Sainan; Wang, Yuejun; Qian, Xin; Asis, Junaidi Bin; Lu, Xianghong; Zhang, Yuzhi; Gan, Chengshi
Graphical abstract: Highlights: Adakites identified in the Bantimala Complex formed at ∼ 87 Ma. The adakites were derived from Neotethyan slab-derived melt. They are generated at the end of subduction in response to the slab break-off. Abstract: The Bantimala Complex in SW Sulawesi is an important part of the Central Indonesian Accretionary Complex in SE Asia, which records the interaction of the Eurasian, Indian-Australian, and Pacific-Philippine plates. Igneous rocks in the complex have recorded important information about the Mesozoic tectonic evolution of SE Asia. This paper documents the Late Cretaceous adakites newly discovered in the Bantimala Complex at Barru. The adakites formed at ∼ 87 Ma, and have SiO2  = 64.38–69.14 wt%, Al2 O3  = 16.16–17.37 wt%, MgO = 4.17–5.82 wt%, K2 O = 0.61–1.88 wt%, Y = 3.09–8.21 ppm, Sr = 320–823 ppm and Sr/Y = 46–179. They show arc-like elemental pattern with Nb-Ta-Ti negative anomalies. The diagnostic elemental and isotopic compositions, including ( 87 Sr/ 86 Sr)i  = 0.70391–0.70423, εNd (t) = +5.11∼+5.68, ( 206 Pb/ 204 Pb)i  = 18.31–18.54, ( 207 Pb/ 204 Pb)i  = 15.58–15.58, ( 208 Pb/ 204 Pb)i  = 38.22–38.38, ɛHf (t)= +13.3 ∼+16.6 and mantle-like δ 18 O = 5.44–6.02 ‰, suggest the slab-derived high-Si melt of the Barru adakites. These data argue for the Tethyan affinity of the Central Indonesian Accretionary Complex. They evidenced the development of Late Cretaceous tectonic reconstruction of SW Sulawesi, and the cease of Neotethyan subduction slab at ∼ 87 Ma beneath the Argoland. The slab-derived Barru adakite was generated in response to Neotethyan slab break-off beneath the Central Indonesian Accretionary Complex.